Covid-19 Pandemic’s Impact on Mental Health - Thalia Audina (Muhammadiyah International Public Health and Medicine Proceeding, 2021)
Background: The Covid-19 pandemic in Indonesia, apart from having an impact on physical health, also has an impact on psychological or mental health. Psychological impacts during the pandemic include post-traumatic stress disorder, depression, anxiety, frustration, fear of infection, insomnia, and feeling helpless. Aim: This study was conducted to determine the impact of Covid-19 on mental health, as well as to find out strategies in dealing with these impacts so that they survive in the Covid-19 pandemic era. Methods: This study uses literature with the object of mental health research during the Covid-19 pandemic, several journal sources and related articles are reviewed and grouped. Results: This study shows that Covid-19 has an impact on mental health by people in various parts of the world. In Indonesia, mental health problems, such as anxiety, depression, trauma due to the Covid-19 pandemic are also being felt in real terms at this time. Conclusions: The COVID-19 pandemic has a major impact on mental health. The government's strategy and community participation are expected to be able to face mental health challenges due to the Covid-19 pandemic.